Use of Validationgram in Counselling: Exploring Sources of Self-Validation and Impact of Personal Transition - Ishiyama, F. Ishu (Canadian Journal of Counselling and Psychotherapy, 2007)
An activity called "validationgram," derived from Ishiyama's (1989) model of self described. Validationgram is a visual activity of mapping sources of validation in four domains (i.e., relationships, activities, things, and places). It is proposed that validationgram is useful in counselling for exploring the client's world of meanings, feelings and values, and for understanding the effects of significant life events and transitions on one's validation system. The activity's underlying assumptions, clinical value, optional modes of application, and potential utility as a research tool are also discussed.